Synthesis and electrocoating of indole–thiophene comonomer on carbon fiber microelectrode, and surface topography by AFM - Sarac, A. Sezai; Ozkara Sarioglan, Serife; Dziomba, Thorsten; Sezer, Esma (Elsevier BV, 2007)
Abstract 5,2-Thiophenylindole(5,2 In–Th) comonomer is synthesized by means of palladium catalyzed Stille cross-coupling reaction with an aim of obtaining extensively conjugated, low oxidation potential comonomer relative to its corresponding monomer. The comonomer is characterized by UV–Visible, FTIR, and NMR spectroscopic techniques, and the resulting conjugated copolymer exhibited the properties of both polyindole and polythiophene (having low oxidation potential and high conductivity). 5,2 In–Th comonomer was electropolymerized onto carbon fiber microelectrodes. The copolymer was electrochemically coated (grafted) onto micron size carbon fiber by constant potential electrolysis and cyclic voltammetry (CV) and the resulting nanosize thin films of polymers were characterized using atomic force microscopy (AFM), and FTIR spectroscopy. The efficiency of the electrocopolymerization process on the carbon fiber surfaces under preparative constant current electrolysis and potentiodynamic conditions, was evaluated in order to ascertain the effects of copolymer thickness, dopant and morphology.